2008
DOI: 10.1080/02699200802394823
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bilateral stimulation of the subthalamic nucleus on different speech subsystems in patients with Parkinson's disease

Abstract: The effect of deep brain stimulation on the two speech-production subsystems, articulation and phonation, of nine Parkinsonian patients is examined. Production parameters (stop closure voicing; stop closure, VOT, vowel) in fast syllable-repetitions were defined and measured and quantitative, objective metrics of vocal fold function were obtained during vowel production. Speech material was recorded for patients (with and without stimulation) and for a reference group of healthy control speakers. With stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 34 publications
(36 reference statements)
0
19
0
1
Order By: Relevance
“…Evidence can be seen in studies that show an increase or slowing down of the speed of movements under medication (Pinto et al, 2004). Concerning speech associated with hypokinetic dysarthria, most studies focus on temporal aspects (Weismer, 1984;Ludlow, Connor, and Bassich, 1987; for an overview see Schirmer, 2004;Farrell, Theodoros, Ward, Hall, and Silburn, 2005;Pützer, Barry, and Moringlane, 2008) but not on spatial articulatory features. Our aim is to use EPG to investigate whether and in what ways the cortico-striatial circuit affects not only the temporal but also the articulatory spatial aspects of speech production in PD.…”
Section: Consonant Production In Pdmentioning
confidence: 97%
See 1 more Smart Citation
“…Evidence can be seen in studies that show an increase or slowing down of the speed of movements under medication (Pinto et al, 2004). Concerning speech associated with hypokinetic dysarthria, most studies focus on temporal aspects (Weismer, 1984;Ludlow, Connor, and Bassich, 1987; for an overview see Schirmer, 2004;Farrell, Theodoros, Ward, Hall, and Silburn, 2005;Pützer, Barry, and Moringlane, 2008) but not on spatial articulatory features. Our aim is to use EPG to investigate whether and in what ways the cortico-striatial circuit affects not only the temporal but also the articulatory spatial aspects of speech production in PD.…”
Section: Consonant Production In Pdmentioning
confidence: 97%
“…Recent studies (e.g. Pützer et al, 2008) reported the presence of fricated stops ([t]) in five out of nine patients ON stimulation. They discussed the differences in fine motor control of apical tongue movements (with[t]) in comparison to those involving the dorsum (e.g.…”
Section: Consonant Production In Pdmentioning
confidence: 99%
“…13,14 Research has shown that medical therapies alone are not as effective for treating speech symptoms as they are for motor functions, 15 and the effect of medical treatment on speech production tends to be individual. [16][17][18] Furthermore, only 3%-4% of PD patients receive speech therapy. 19 Behavioral speech therapy, including intensive voice treatment, appears to be the most effective type of speech intervention in the early and moderate stage of PD at present.…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches have been chosen to study biolinguistic effects of DBS, comprising the assessment of language under active versus inactive stimulation, under variation of DBS parameters and before versus after surgery (Bordini, Garg, Gallagher, Bell, & Garell, 2007;Carpenter et al, 1998;D'Alatri et al, 2008;Klostermann et al, 2008;Puetzer, Barry, & Moringlane, 2008;Rousseaux et al, 2004;Saint-Cyr, Trépanier, Kumar, Lozano, & Lang, 2000;Santens, De Letter, Van Borsel, De Reuck, & Caemaert, 2003;Toernqvist, Schalén, & Rehncrona, 2005;Tripoliti, Limousin, Tisch, Borrell, & Hariz, 2006;Tripoliti et al, 2008;Wang et al, 2006). Most of these studies were performed under clinical rather than neuroscientific aspects, the major concern being the safety of the therapeutic procedure (Ardouin et al, 1999;Dujardin, Defebvre, Krystkowiak, Blond, & Destee, 2001;Saint-Cyr & Albanese, 2006;Saint-Cyr et al, 2000).…”
Section: Effects Of Dbs On Language Functionsmentioning
confidence: 98%